Large Vessel Disease Modifies the Relationship Between Kidney Injury and Cerebral Small Vessel Disease - Ao, Dong-Hui; Zhai, Fei-Fei; Han, Fei; Zhou, Li-Xin; Ni, Jun; Yao, Ming; Zhang, Ding-Ding; Li, Ming-Li; Fan, Xiao-Hong; Jin, Zheng-Yu; Cui, Li-Ying; Zhang, Shu-Yang; et al. (Frontiers in Neurology, 2018)
Abstract Background: Recent studies have shown that renal disease is associated with magnetic resonance imaging (MRI) markers of cerebral small vessel disease (CSVD), independent of traditional vascular risk factors. Although large artery lesions might be involved in the cerebrorenal association, evidence has been lacking. Methods: A total of 928 participants from a population-based cohort study were included. Kidney injury measurements included urinary albumin-to-creatinine ratio (ACR) and estimated glomerular filtration rate (eGFR). CSVD was assessed on MRI by white matter hyperintensity volume (WMHV), lacunes, brain parenchymal fraction (BPF), cerebral microbleeds (CMBs), and perivascular space. Carotid plaques and brachial-ankle pulse wave velocity (baPWV) were used to assess large artery atherosclerosis and stiffness. Multivariable linear and logistic regression and additional interaction models were used for statistical analysis. Results: Individuals with elevated ACR had higher prevalence of lacunes and more WMHV (p=0.001 and 0.000 respectively), those with decreased eGFR had smaller brain volume, higher prevalence of lacunes and deep CMBs (p=0.009, p=0.017) and p=0.010 respectively). Interaction analysis revealed that carotid plaque and baPWV significantly enhanced the association between eGFR and BPF (p=0.001 and p=0.002 respectively), that is，the association of eGFR with BPF was only significant among participants with carotid plaque and higher baPWV. In addition, carotid plaque enhanced the association between ACR and WMHV (p=0.034) and baPWV enhanced the association between ACR and the presence of lacunes (p=0.027). Modifying effect of large vessel disease markers on the association between kidney injury measurements and CMBs was not significant. Conclusion: Evaluation of subclinical CVSD in individuals with kidney injury is warranted, especially in those with combined large artery disease.